If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 4) = 6(2) Reorder the terms: x(4 + x) = 6(2) (4 * x + x * x) = 6(2) (4x + x2) = 6(2) Multiply 6 * 2 4x + x2 = 12 Solving 4x + x2 = 12 Solving for variable 'x'. Reorder the terms: -12 + 4x + x2 = 12 + -12 Combine like terms: 12 + -12 = 0 -12 + 4x + x2 = 0 Factor a trinomial. (-6 + -1x)(2 + -1x) = 0Subproblem 1
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-6, 2}
| 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 | | -41=5x+9 | | -1440=-15(-15x-21) | | 1.4a+10=17 | | 6x+13=5x | | n+36=5m | | (X-3)(x+4)=x^2-5x+20 | | 9+2z-8=7z+7-4z | | a(-12)=b | | 0.6x-0.33=1 | | 4000=5.5x-460.5 | | x+16=2x-16 | | v=3.141592654(36)(16) | | 8(t-3)+4=4(3t+5)-9 |